Presidential Threshold Ditinjau dari Undang-Undang Dasar Republik Indonesia Tahun 1945 - Fernando Anggrek; Hesti Armiwulan; Didik Widitrismiharto (Keluwih: Jurnal Sosial dan Humaniora, 2022)
Abstract— Presidential Threshold provisions which are used as additional requirements for political parties to be able to carry pairs of candidates for President and Vice President in a general election. Political parties by the 1945 Constitution of the Republic of Indonesia are given the right to be able to independently or join other political parties (political party coalitions) to be able to nominate pairs of candidates for President and Vice President. Normatively, political parties are given rights by the constitution but since the enactment of the Presidential Threshold provisions, the constitutional rights of political parties cannot be fully implemented. With this provision, political parties may lose their rights as regulated in the constitution. This condition makes the Presidential Threshold provision contrary to the 1945 Constitution of the Republic of Indonesia. Keywords: presidential threshold, political parties,general election. Abstrak— Ketentuan Presidential Threshold yang dijadikan syarat tambahan bagi partai politik untuk dapat mengusung pasangan calon Presiden dan Wakil Presiden dalam sebuah pemilihan umum. Partai politik oleh UUD Negara RI 1945 diberikan hak untuk dapat secara mandiri atau bergabung dengan partai politik lain (koalisi partai politik) untuk dapat mengusung pasangan calon Presiden dan Wakil Presiden. Secara normatif, partai politik diberikan hak oleh konstitusi namun sejak berlakunya ketentuan mengenai Presidential Threshold, hak konstitusi partai politik tersebut tidak dapat dilaksanakan sepenuhnya. Dengan adanya ketentuan tersebut, partai politik dapat kehilangan haknya sebagaimana telah diatur dalam konstitusi. Kondisi tersebut membuat ketentuan Presidential Threshold bertentangan dengan UUD Negara RI 1945. Kata kunci: presidential threshold, partai politik, pemilihan umum